Hierarchically Porous Metal–Organic Frameworks: Synthetic Strategies and Applications. Issue 1 (30th October 2022) - Yao, Yao; Zhao, Xinyu; Chang, Ganggang; Yang, Xiaoyu; Chen, Banglin
Abstract : Metal–organic frameworks (MOFs), assemblies comprised of metal nodes and organic ligands, have captured the interest of scientists during the past two decades. The flexible approaches developed for the custom design of framework structures and intriguing pore‐containing environments formed at the molecular or atomic level have elevated the interest in MOFs to a level that is far beyond those of traditional porous solids (e.g., zeolites, activated carbon). Nevertheless, applications of MOFs, particularly in the process involving large molecules, have been restricted by narrow pore size. To overcome the restriction imposed by the micropores, a great effort has been given to related hierarchically porous MOFs (HP‐MOFs), which combine high surface areas of microporous materials with the spaces of meso‐/macropores that allow accessibility and diffusivity by large molecules. This review focuses on recent advances and breakthroughs in the design and synthesis of HP‐MOFs that contain intrinsic pores, defective pores, and pores based on interparticle accumulation, respectively. In addition, the applications of HP‐MOFs in heterogeneous catalysis, water remediation, gas storage and separation, biotechnology, energy storage, and sensing are summarized from the perspective of the relationships between synthetic strategies and applications. Finally, challenging and promising research directions in the field of HP‐MOFs are discussed. Abstract : This review focuses on recent advances in the design and synthesis of hierarchically porous metal–organic frameworks (HP‐MOFs) that contain intrinsic pores, defective pores, and pores based on interparticle accumulation, respectively. And applications of HP‐MOFs in heterogeneous catalysis, water remediation, gas storage and separation, biotechnology, energy storage, and sensing are summarized from the relationships between synthetic strategies and applications.